PENGARUH MINAT DAN KEMANDIRIAN BELAJAR TERHADAP KOMPETENSI MATA PELAJARAN EKONOMI KELAS XI SMA NEGERI 8 PONTIANAK - Syarkiyah, Kiki; Herkulana, Herkulana; Achmadi, Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract : This research concerns on the Influence of Interest and Independence Learning on the Â Competence of Economics Subject Students in Grade XI SMA Negeri 8 Pontianak. The problems that will be studied is to know and analyze (1) the influence of learning interest on the competence of economic subjects (2) the influence of learning independence on the competence of economic subjects (3) the influence of learning interest on the independence of learning (4) the influence of interest and learning independence on subject competence. The data collected in this study are analyzed using quantitative analysis. The population in this research is all students of XI Class who are Interested Economics of Â SMA Negeri 8 Pontianak which and they are 48 students. The data collection tool in this research is the guidance of observation, questionnaire worksheet for documentation. Data analysis technique used is through quantitative calculation, classical assumption test and analyzed using multiple linear regression analysis. The results showed that (1) there is a partial interest influence on the competence of economic subjects (2) there is influence of partial learning independence to the competence of economics subject (3) there is influence of partial learning interest to the independence of study (4) there is influence of interest and independence of study partially to student's competence on economic subject 37,1%.Keywords: Interest, Learning Independence, Competence